2000
DOI: 10.1007/s11746-000-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

The specific gravity of biodiesel and its blends with diesel fuel

Abstract: The specific gravities of biodiesel and 75, 50, and 20% blends with No. 1 and No. 2 diesel fuels were measured as a function of temperature from the onset of crystallization to 100°C. The results indicate that biodiesel and its blends demonstrate temperature-dependent behavior that is qualitatively similar to the diesel fuels. The temperature dependence of the specific gravity for biodiesel and its blends was compared with the ASTM D 1250-80 procedure for the temperature correction of hydrocarbon fuels, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
112
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 3 publications
5
112
0
1
Order By: Relevance
“…Specific gravity is defined as a ratio of the density of a given solid or liquid substance to the density of water at a specific temperature and pressure, typically at 4°C and 1atm. Tat and Garpen [10] measured experimentally the specific gravity of 20%, 50%, 75%, and 100% soyabean biodiesel as a function of temperature in the temperature range of crystallization temperature to 100 o C using the standard hydrometer method. The results indicate that the biodiesel and its blends demonstrate temperature dependent behaviour.…”
Section: Density Of Biodieselmentioning
confidence: 99%
See 4 more Smart Citations
“…Specific gravity is defined as a ratio of the density of a given solid or liquid substance to the density of water at a specific temperature and pressure, typically at 4°C and 1atm. Tat and Garpen [10] measured experimentally the specific gravity of 20%, 50%, 75%, and 100% soyabean biodiesel as a function of temperature in the temperature range of crystallization temperature to 100 o C using the standard hydrometer method. The results indicate that the biodiesel and its blends demonstrate temperature dependent behaviour.…”
Section: Density Of Biodieselmentioning
confidence: 99%
“…Tat et al [4] also reported similar linear equation for three different biodiesels namely, canola-oil biodiesel, soyabean-oil biodiesel and fish-oil biodiesel. These equations were developed based on the data obtained from a capacitance type liquid level meter within temperature range of 20 o C to 300 o C. Clements (referenced in [10]) suggested that equation (2) can be used to determine the specific gravity of different biodiesel blends at a standard temperature. In this equation the specific gravity of the blend has been considerd to be proportional to mass fractions of the constituents.…”
Section: Density Of Biodieselmentioning
confidence: 99%
See 3 more Smart Citations